Design and Implementation of an Ultrasonic Sensor-Based Blind Spot Monitoring Prototype for Vehicle Safety - Fikri Arif Wicaksana; Trisiani Dewi Hendrawati; Panji Narputro; Muhammad Raihan Usman (Journal of Electrical, Electronic, Information, and Communication Technology, 2025)
Blind spots are one of the main contributing factors to traffic accidents in four-wheeled vehicles due to the driver’s limited visibility in certain areas surrounding the vehicle. This research presents the design and implementation of a blind spot monitoring prototype using ultrasonic sensors to detect objects in blind spot areas and provide real-time warnings to the driver. The system consists of four ultrasonic sensors (HC-SR04 for the front and JSN-SR04T for the sides and rear), an Arduino Mega 2560 microcontroller, a 20×4 LCD for distance display, and a buzzer for audible alerts. Sensor calibration was conducted to ensure measurement accuracy, achieving an average error rate of 0.77%. The prototype was tested under various simulated scenarios, including static and moving objects in different blind spot zones. The results show that the system successfully detected vehicles, motorcycles, and pedestrians in almost all testing conditions, with an average response time ranging from 0.20 to 0.35 seconds. However, the system faced limitations in detecting objects moving at speeds above 30 km/h, which is inherent to ultrasonic sensor technology. Despite this limitation, the proposed system offers a cost-effective alternative to radar- or camera-based blind spot detection systems, making it more accessible for a wider range of vehicles. The findings indicate that the developed prototype can effectively improve driving safety and has the potential for further enhancement through integration with IoT and advanced sensor fusion technologies.